SUSTAINABILITY AND THE RURAL ENTERPRISE ECONOMY economic, environmental. (ROUTLEDGE, 2026)
Enterprises in rural regions must now act in a globalized world and face global challenges, such as climate change, resource scarcities and social inequalities or the sustainability preferences of consumers. Rural start-up enterprises often strive to contribute to the solutions of global-scale problems, for example, the issues expressed by the United Nations Sustainable Development Goals, and for getting skilled labor into urban regions in order to make rural regions appealing to young people again. This book explores the management of sustainability issues in the context of the rural enterprise economy.It sheds light on these challenges and opportunities by linking the rural enterprise economy and sustainability management. It provides practical evidence about how rural enterprises and rural entrepreneurs can handle sustainability requirements and contribute to sustainability transformations in terms of economic, environmental and social stability. In addition to its practical relevance, the motivation of the book is first and foremost to develop a common understanding of the necessary key terminology and core concepts in a still largely underexplored, yet rapidly expanding research field and contribute to theory development by employing a multidisciplinary approach. It offers state-of-the-art cases from various countries to question and approach unresolved research questions related to sustainability issues and the management of sustainability, which are both a requirement and an opportunity for entrepreneurs and enterprises in a rural context.The book primarily targets scholars and researchers in economics and business research, entrepreneurship, innovation, regional planning, economic geography and sustainability management. It is also aimed at practitioners committed to enterprise development or entrepreneurship in rural regions and elsewhere, and policymakers and policy actors at different levels.
Keywords: Rural development -- Environmental aspects.; Sustainable development.; elektronické knihy; electronic books